Simple screen locking method using randomly generated number grid on image - Aris H.; Ibrahim Z.; Azman A. (IGI Global, 2023)
Smartphones have become part and parcel of our daily life. Due to the more and more advanced features incorporated, its role has extended beyond calls and text messages, and it has become a place where important personal information is being stored. Thus, it needs to be protected from unauthorised users, which is usually achieved by using screen locking. However, improved screen locking security often compromises other aspects, such as usability and cost. In this article, a new screen locking method (SyS) that is both simple, secure from shoulder surf and smudge attacks, and not expensive to implement is presented. It uses an image and a chosen number to create the screen locking code. Evaluation results show that the SyS screen lock method scores best in terms of usability and security compared to the other three common screen locking methods, namely personal identification number or PIN, password, and pattern. It also performs well theoretically when compared against existing screen locking methods that aim at defending against similar attacks. Copyright 2018, IGI Global.